Content, Language and Technology: Perspectives and Prospects - Mohanraj, S (Journal of NELTA, 2018)
Introduction: Language learning is probably as ancient as human kind. Man has been communicating in one form or the other since the time he evolved. Such means of communication has undergone a process of evolutionary changes to stabilize as language and provide an identity to its user. With language becoming the principal source of interaction, the man in his curiosity and wisdom, began to analyse it to facilitate teaching/learning of the same easily. The present article is a conclave of such attempts (researches) and takes into account a historical perspective. While doing so an attempt has been made to discuss topics such as Second Language Acquisition (SLA), Continuing Professional Development (CPD) and Information Communication Technology (ICT).